Laser deposition of compositionally graded titanium oxide on Ti6Al4V alloy. Issue 17 (1st December 2018) - Lu, Mingyuan; McCormick, Paul; Zhao, Yitian; Fan, Zhiqi; Huang, Han
Abstract: In this study, a laser cladding process was developed to deposit dense and well-adhered titanium single tracks on the surface of Ti6Al4V alloy with a compositional and microstructural gradient. CuO doped, freeze-dried anatase powder was specially formulated for this process. The addition of CuO resulted in stable melt pool with low viscosity, low surface tension and enhanced wettability with the substrate. Continuous titanium oxide single tracks were formed with a cross-sectional profile that was advantageous for coating deposition by means of multiple overlapping scan tracks. Rapid heating and cooling associated with laser cladding produced unique solidified microstructures with a compositional gradient. No structurally critical fractures were observed in the graded oxide layers, or at the coating/substrate interfaces. Furthermore, a transition zone of oxide/metal mixture was observed at the interface, increasing the effective bonding area between the coating and the substrate.